Comparison of cervical cancer screening by self-sampling papillomavirus test versus pap-smear in underprivileged women in France. - Reques, Laura; Rolland, Camille; Lallemand, Anne; Lahmidi, Najat; Aranda-Fernández, Ezequiel; Lazzarino, Antonio; Bottero, Julie; Hamers, Françoise; Bergeron, Christine; Haguenoer, Ken; Launoy, Guy; Luhmann, Niklas (BMC Women's Health, 2021)
Background: The purpose of this study was to compare cervical cancer screening by pap smear (PS) versus preliminary HPV testing based on self-collected samples (SC-HPV).Methods: Interventional study among underprivileged women from 25 to 65 years old in four French cities. The control group (CG) was referred for a PS. The experimental group (EG) conducted a SC-HPV test followed by a PS in case of positivity. Differences on screening completion and cytological abnormalities were analysed by logistic and Cox regression.Results: 383 women were assigned to the EG and 304 to the CG. The screening completion proportion was 39.5% in the CG compared to 71.3% in the EG (HR = 2.48 (CI 95% [1.99-3.08]; p < 0.001). The proportion of cytological abnormalities was 2.0% in the CG and 2.3% in the EG (OR = 1.20 (CI 95% [0.42-3.40]; p = 0.7). The proportion of participants lost to follow-up was 60.5% in the CG and 63.2% in the EG HPV positive (p = 0.18).Conclusion: Providing an SC-HPV-test increased the participation of underprivileged women in CCS. Nevertheless, the significant number of lost to follow-up in both groups can undermine the initial benefits of the strategy for HPV positive women. Registration: Clinicaltrials.gov: NCT03118258.